The (Biological or Cultural) Essence of Essentialism: Implications for Policy Support among Dominant and Subordinated Groups - Soylu Yalcinkaya, Nur; Estrada-Villalta, Sara; Adams, Glenn (Frontiers in Psychology, 2017)
Most research links (racial) essentialism to negative intergroup outcomes. We propose that this conclusion reflects both a narrow conceptual focus on biological/genetic essence and a narrow research focus from the perspective of racially dominant groups. We distinguished between beliefs in biological and cultural essences, and we investigated the implications of this distinction for support of social justice policies (e.g., affirmative action) among people with dominant (White) and subordinated (e.g., Black, Latino) racial identities in the United States. Whereas endorsement of biological essentialism may have similarly negative implications for social justice policies across racial categories, we investigated the hypothesis that endorsement of cultural essentialism would have different implications across racial categories. In Studies 1a and 1b, we assess the properties of a cultural essentialism measure we developed using two samples with different racial/ethnic compositions. In Study 2, we collected data from 170 participants using an online questionnaire to test the implications of essentialist beliefs for policy support. Consistent with previous research, we found that belief in biological essentialism was negatively related to policy support for participants from both dominant and subordinated categories. In contrast, the relationship between cultural essentialism and policy support varied across identity categories in the hypothesized way: negative for participants from the dominant category but positive for participants from subordinated categories. Results suggest that cultural essentialism may provide a way of identification that subordinated communities use to mobilize support for social justice.